Minimally invasive radioguided parathyroid surgery: A literature review. (April 2016) - Desiato, Vincenzo; Melis, Marcovalerio; Amato, Bruno; Bianco, Tommaso; Rocca, Aldo; Amato, Maurizio; Quarto, Gennaro; Benassai, Giacomo
Abstract: The minimally invasive approach to parathyroid glands represents an important field of application of radioguided surgery. As always happens, in all cases pertaining to hyper-specialized skills, scientific production has long been the prerogative of a few Authors, but the ever increasing technological diffusion, combined with excellent results often achieved, increases the interest in this technique. This is particularly true in the era of minimally invasive surgery. The Authors realize a review of the existing literature to allow an overall view of current knowledge on this particular topic and to guide future research.